(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
With a growing interest in meditation as a means of enhancing overall well-being, it is essential to understand the effects of meditation on mental health outcomes. The review reveals consistent findings indicating that meditation practices have a positive impact on mental health and well-being. Cross-sectional studies demonstrate that individuals who engage in regular meditation exhibit lower levels of anxiety, depression, and perceived stress. Controlled studies, including randomized controlled trials, provide stronger evidence, showing that meditation interventions effectively reduce symptoms of mental health disorders and improve psychological well-being. Intervention studies further highlight the benefits of meditation practices in improving attention, cognitive functioning, emotional regulation, and overall subjective well-being. The findings suggest that meditation practices can be valuable tools for promoting mental health and well-being. It highlights the potential of meditation as an effective approach for reducing symptoms of mental health disorders, enhancing psychological well-being, and improving overall quality of life. However, there are areas in need of further research, such as understanding the underlying mechanisms of action, determining optimal dosage and duration of meditation practice, and exploring the long-term effects of meditation.